CFD simulation of water diffusion in fruit drying: Case of apricot hemispheres - Sempou Alkistis; Lentzou Diamanto; Athanasiou Athanasios; Boudouvis Andreas; Xanthopoulos Georgios (E3S Web of Conferences)
Food drying is a storage process during which the available water is removed. The present analysis conducted for three drying temperatures 45, 55 and 65 °C and the effective water diffusivity was estimated as 1.69×10-10, 2.91×10-10 and 6.67×10-10 m2/s. Comsol Multiphysics 4.3b was used to model the problem and simulate the process. The apricot hemispheres shrinkage was modelled as function of moisture content reduction. The results showed that water diffusivity, the mass transfer coefficient between the fruit surface and drying air and the activation energy of the process increase with drying temperature. The mass transfer coefficient, km, was estimated as 1.0×10-5, 9.98×10-5 and 0.85×10-2 m/s at 45, 55 and 65 °C. The estimated activation energy was 59.6, 59.9 and 60.8 kJ/mol at 45, 55 and 65 °C. The average relative error between experimental and computational moisture content was 0.47, 0.88 and 1.32% at 45, 55 and 65 °C. The Levenberg-Marquardt (L-M) and Sparse Non-Linear Optimizer (SNOPT) optimization algorithms were implemented.